Austria : Austria: Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper discusses structural and fiscal reforms in Austria that could increase potential output. Structural measures focused on further liberalization of professional services, and lowering of the barriers to trade and investment to increase potential output. Although Austria is among the countries with least restrictive business environment, there is a room for further improvement. The policy recommendations focus mostly on startups, professional services (legal, accounting, architecture, and engineering professions), competition in network industries, and barriers to foreign direct investment, resulting in an estimated impact of roughly 1.5 percent of GDP in the medium term.